Nowe badania archeologiczne na Śródce w Poznaniu - Pawlak, Paweł; Wesołowska, Paulina (Ecclesia. Studia z Dziejów Wielkopolski, 2014)
Archaeological research conducted in the years 2012-2013 at Śródka in Poznań provided some crucial information that enriches our knowledge on the past of the city. During twenty years of excavations carried out in that area of the city we managed to unearth a large part of an early medieval burial ground where the inhabitants of the gord were buried from the end of the 10th century until the end of the 12th century. The location of the cemetery was preceded by resettlement of the residents of an extensive hamlet employed in craftsmanship and trade to new sites (another region of Śródka and perhaps also to the territory of Zagórze). Demarcation of the burial site most likely had a propaganda dimension connected with the process of constitution of Christian rites which also included the funeral sphere. Archaeological research conducted in the years 2012-2013 at Śródka in Poznań provided some crucial information that enriches our knowledge on the past of the city. During twenty years of excavations carried out in that area of the city we managed to unearth a large part of an early medieval burial ground where the inhabitants of the gord were buried from the end of the 10th century until the end of the 12th century. The location of the cemetery was preceded by resettlement of the residents of an extensive hamlet employed in craftsmanship and trade to new sites (another region of Śródka and perhaps also to the territory of Zagórze). Demarcation of the burial site most likely had a propaganda dimension connected with the process of constitution of Christian rites which also included the funeral sphere. Another discovery which is of exceptional significance for the history of Śródka and Poznań is the finding of remnants of a workshop run by bell founding masters specializing in casting bells. It is the second workshop of this type unearthed by us on this site. It is worth underscoring that to date those are the oldest remnants of bell founding workshops in Poland evidenced by excavations.